Low Reynolds number stability of MHD plane Poiseuille flow of an Oldroyd fluid - R. N. Ray; A. Samad; T. K. Chaudhury (International Journal of Mathematics and Mathematical Sciences)
The linear stability of plane Poiseuille flow at low Reynolds number of a conducting Oldroyd fluid in the presence of a transverse magnetic field has been investigated numerically. Spectral tau method with expansions in Chebyshev polynomials is used to solve the Orr-Sommerfeld equation. It is found that viscoelastic parameters have destabilizing effect and magnetic field has a stabilizing effect in the field of flow. But no instabilities are found.